Electrical characteristics of large state-of-the-art electrochemical capacitors. (1st June 2019) - Miller, John R.; Butler, S.M.
Abstract: Electrochemical capacitor (EC) technology has advanced considerably since the first products were commercially introduced more than forty years ago. Products today, on both a mass and a volume basis, store considerably more energy and deliver significantly higher power than did the earlier ECs. Plus products today are available with much higher ratings. Today modules containing many kF-sized ECs are used to store energy in a wide variety of industrial applications. Worldwide, fifty companies are estimated to manufacture EC products. This paper reports initial electrical characteristics of eight popular, state-of-the-art electrochemical capacitor cells. Large-signal, small-signal, and functional-test performance is compared among these ECs. A goal was to identify fundamental strengths of each of the eight technologies as expressed by the eight samples evaluated.